2012
DOI: 10.1149/2.061208jes
|View full text |Cite
|
Sign up to set email alerts
|

Thin Composite Films of Mussel Adhesive Proteins and Ceria Nanoparticles on Carbon Steel for Corrosion Protection

Abstract: Thin composite films of the mussel adhesive proteins (Mefp-1) and ceria nanoparticles were deposited on substrate surfaces by alternating immersions. The film formation was studied by quartz crystal microbalance with dissipation (QCM-D) monitoring. Both the changes in frequency and dissipation recorded by QCM-D demonstrate buildup of a composite film of Mefp-1 and nanoceria. Micro-and nanostructure and composition of the film on carbon steel were characterized by optical and atomic force microscopy (AFM), elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…2a, shows that the Mefp-1 related spectrum is almost identical to the one obtained in air [24]. This indicates very limited corrosion product formation within this short exposure period.…”
Section: Crm Characterization Of the Mefp-1/ceria Composite Filmsupporting
confidence: 53%
See 3 more Smart Citations
“…2a, shows that the Mefp-1 related spectrum is almost identical to the one obtained in air [24]. This indicates very limited corrosion product formation within this short exposure period.…”
Section: Crm Characterization Of the Mefp-1/ceria Composite Filmsupporting
confidence: 53%
“…In this regard, it was reported that ceria nanoparticles are not cytotoxic but instead protect cells from oxidation insult [23]. In our previous study [24], a thin composite film of Mefp-1 and ceria nanoparticles was shown to exhibit significant corrosion protection for carbon steel in NaCl containing phosphoric acid. A combination of both ex situ and in situ techniques has been used to investigate the film formation, structure and corrosion inhibition performance.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…7 Previous investigations have indicated that DOPA-containing proteins are capable of inhibiting corrosion to various degrees on some metals. 1,[8][9][10][11][12][13] In addition to this, DOPA can participate in crosslinking reactions as a result of chemical or enzymatic oxidation. When oxidized, DOPA forms a quinone-intermediate, which can in turn react further with catechol groups or nucleophiles present elsewhere in the protein to form a crosslinked protein.…”
mentioning
confidence: 99%